Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Makanan Kripik Seblak Bantet (Studi Kasus Masyarakat Desa Bumiharjo) - Dewi Arnum Sari; Annisa Syahdila Malik Batu Bara (-, 2021)
ABSTRACTThe purpose of this study was to determine whether product quality and price had a major influence on purchasing decisions in the village of Bumi Harjo, sub-district of Buay Buhaga. The method used in this research is the method of collecting questionnaire data and data analysis. The results of this study show that product quality and price variables have a significant and significant influence on purchasing decisions.Keywords: Product Quality, Price, Purchase Decision